2021
DOI: 10.1021/acs.inorgchem.1c00104
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Recognition by Flexible Coordination Polymers of Ag+ with a Cysteine-Based Chiral Thiol Ligand That Bears a Binding Site

Abstract: We report a new scheme for chiral recognition using coordination polymers of Ag+ with a chiral thiol ligand that contains a binding group. N-Benzoyl-l-cysteine ethyl ester equipped with a boronic acid group at the para position of the phenyl ring forms coordination polymers with Ag+ in alkaline aqueous solutions that exhibit excellent selectivity toward a d-glucose enantiomer over l-glucose, while the coordination polymers from the d-cysteine-based thiol ligand are specific for l-glucose. It is assumed that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…However, this substantially complicates the syntheses. Although many chiroptical diboronic acid-based receptors exhibit changes in circular dichroism spectra, most of them show no fluorescence response. , James et al reported a fluorescent binaphthyl diboronic acid-based receptor for the chiral recognition of d -glucose in methanol/water (1/2) with a D/L fluorescence intensity ratio of only 1.93 . Heinrichs et al developed a chiral macrocyclic diboronic acid-based receptor that shows chiral selectivity for d -glucose with turn-off response in methanol/water (1/1), requiring seven steps of complicated synthesis .…”
mentioning
confidence: 99%
“…However, this substantially complicates the syntheses. Although many chiroptical diboronic acid-based receptors exhibit changes in circular dichroism spectra, most of them show no fluorescence response. , James et al reported a fluorescent binaphthyl diboronic acid-based receptor for the chiral recognition of d -glucose in methanol/water (1/2) with a D/L fluorescence intensity ratio of only 1.93 . Heinrichs et al developed a chiral macrocyclic diboronic acid-based receptor that shows chiral selectivity for d -glucose with turn-off response in methanol/water (1/1), requiring seven steps of complicated synthesis .…”
mentioning
confidence: 99%
“…d -cysteine ( d -cys), an enantiomer of natural l -cysteine ( l -cys), has been proved to significantly inhibit the growth of Gram negative E. coli by inhibiting the activity of threonine deaminase, which may further affect the synthesis of isoleucine, leucine and valine in bacteria [ 36 , 37 , 38 ]. In spite of this, d -cys is not widely used in practical applications because of its inefficient antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the resulting aspartic acid derivatives combine a connecting module (carboxylate groups), a flexible module (succinic acid backbone), a rigid and functional module (conjugated aryl groups), as well as a chiral module (chiral C atom). They may be used as building blocks to assemble homochiral CPs, which are a promising class of materials with various applications in chirotechnology and optoelectronics (Dong et al, 2021;Wang et al, 2012;Wen et al, 2013;Kee & Ok, 2021).…”
Section: Introductionmentioning
confidence: 99%